A validation methodology for urea spray on selective catalytic reduction systems - GÜL, MEHMET ZAFER (My University, 2022)
Selective catalytic reduction (SCR) is an emission control method that reduces the NOx emission using urea sprays as ammonia precursors for exhaust after-treatment systems. The urea injection system is an essential component of the SCR systems. A comprehensive SCR modeling approach is required to design compact after-treatment systems that meet the NOx emission legislation level. In this study, the characteristics of urea spray injectors of the SCR system were investigated using computational fluid dynamics (CFD) and the particle image velocimetry (PIV) technique. A validation strategy was developed to model the urea spray evaporation, liquid/wall contact, and formation of solid urea deposits. The sheet atomization model was modified to improve the performance of the CFD model. While the Rosin-rammler method predicted the results of 10% according to the experimental results, the proposed tabular method decreased the difference by 3%. In addition, 500 parcels were determined as an optimum number of parcels for urea spray according to the sensitivity study. Therefore, the validation methodology was proposed to predict more consistent results for urea spray modeling and the formation of solid urea deposits.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MEKANİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MECHANICS; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Engineering (miscellaneous); Physical Sciences; Selective catalytic reduction; Urea Spray; CFD; PIV; Visualization; DIESEL; COMBUSTION; NITROGEN; Selective catalytic reduction; Urea Spray; CFD; PIV; Visualization